2016
DOI: 10.1097/sla.0000000000001856
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Chemical Thromboprophylaxis and Deep Vein Thrombosis in Major Colorectal Surgery

Abstract: Clinicaltrials.gov #NCT01976988.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
3
22
1
1
Order By: Relevance
“…While previously reported rates of occult DVT are variable, these results are consistent with some of the larger analyses. 4,[14][15][16][17] The 30-day incidence of pulmonary embolism was 2.0% (0.6% to 4.6%), which is consistent with reported outcomes in surgical oncology patients drawing on data from the American College of Surgeons National Surgical Quality Improvement Program. 22 While no pulmonary emboli occurred in patients with occult DVT who were anticoagulated or had a vena cava filter placed, three pulmonary emboli occurred in patients with negative screening duplex and two occurred in patients with distal DVT who were not therapeutically anticoagulated.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…While previously reported rates of occult DVT are variable, these results are consistent with some of the larger analyses. 4,[14][15][16][17] The 30-day incidence of pulmonary embolism was 2.0% (0.6% to 4.6%), which is consistent with reported outcomes in surgical oncology patients drawing on data from the American College of Surgeons National Surgical Quality Improvement Program. 22 While no pulmonary emboli occurred in patients with occult DVT who were anticoagulated or had a vena cava filter placed, three pulmonary emboli occurred in patients with negative screening duplex and two occurred in patients with distal DVT who were not therapeutically anticoagulated.…”
Section: Resultssupporting
confidence: 80%
“…24 Indeed, the rate of preexisting DVT is not insignificant amongst surgical patients. 14,16,17 Identification of preexisting DVT could influence timing of surgery and allow optimal management of perioperative anticoagulation or selective placement of retrievable vena cava filters but would not identify perioperative events. Screening also failed to identify a precedent event in three patients who developed subsequent postoperative PE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 In present study author gave thromboembolic prophylaxis for patients preoperatively and extended 4 weeks postoperatively without minor or major postoperative haemorrhage like other study with follow up 30 days post-surgery. 19 There was no significant difference in preoperative versus postoperative thromboembolic prophylaxis regarding postoperative DVT 0/15(0%) vs 1/15 (13.3%); P = 0.69, and the suspected cause in the case who developed DVT one week postoperatively due to immobilization and obesity inspite of postoperative venous thromboembolic prophylaxis like other study with venous thromboembolic prophylaxis given within 24 hours of colorectal cancer surgery showing lowest rates of adverse events and other study showed that both unfractionated heparin and low-molecular-weight heparin can effectively reduce the incidence of venous thromboembolism in colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%